The Hatoyama Dynasty - Itoh, M. author. aut Link
XXIII, 286 p.
Keywords: This is a multi-generational political history of the Hatoyamas, a family that has participated at the highest levels of Japan's parliamentary government from its inception in the late 1800s. The Hatoyama family is one of the most prominent political families in modern Japanese government. It has produced six members of the Diet, Japan's parliament, many of whom have served as cabinet members and party leaders. Due to the family's political legacy, they have often been likened to the Kennedy family in American politics (though they have been spared the tragedy and scandal visited upon the Kennedys). Despite the significance of the Hatoyamas to modern Japanese politics, this is the first comprehensive study available in English. In tracing the rising political fortunes of this family, it is also possible to study the role of hereditary politicians in Japan, the growth and evolution of Japanese political parties, and, perhaps most importantly, the way political leadership functions in Japan, a society known more for consensus-building than strong leaders.